Current perspectives and trends in colorectal cancer and cancer-associated fibroblasts: a review and bibliometric analysis - Qian, Chengyong; Ren, Lingling; Zhu, Shuyuan; Chen, Fangling; Shen, Haiping; Hu, Xiangcheng; Chen, Guanglan (Frontiers in Immunology, 2025)
BackgroundCancer-associated fibrocytes (CAFs), a key component of the tumour microenvironment, are marked by their heterogeneity. They also exhibit a high degree of plasticity. In the last two decades there has been a strong association established between CAFs and colorectal carcinoma (CRC). However, there are no comprehensive statistics on CRC or CAFs, and the potential directions for research.MethodsThe study performed a literature review spanning from January 1, 2004, to March 27, 2025, within the Web of Science Core Collection Database. VOSviewer and CiteSpace software were used to perform bibliometric analysis and visualization. Microsoft Excel and R was also utilized.ResultsThe analysis included 1145 articles. The articles in question were published across 359 different journals, and included 4032 keywords. The number of publications increased significantly between 2010 and 2025. China was the leading contributor to the total number of publications, and the United States led the global list of citations. Sun Yat-sen University and Shanghai Jiao Tong University are renowned research institutions. Notable researchers such as De Wever, Olivier and Bracke, Marc from Ghent University Hospital, and Pena, Cristina from Puerta de Hierro Majadahonda University Hospital are among the most productive and highly cited authors. CANCERS has the most publications, and the highest citation rate. CAFs are a major focus of research in CRC. This includes the effect of CAFs, such as on cell proliferation and angiogenesis.ConclusionThis study uses bibliometric analyses to present a comprehensive view of research in CAFs, CRCs from 2004 until March 27, 2025. The study highlights important research areas, anticipates future directions and offers valuable insights to future efforts in the field.